Dinamika Permasalahan Individual Siswa dalam Pembelajaran Pendidikan Agama Islam dan Strategi Penanganannya di Sekolah Dasar - Dila Ayu Santika Ritonga; Nur Anisah Nasution; Nur Azizah (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
The development of digital technology has facilitated students in accessing religious information through social media and the internet; however, not all of this information contains values of religious moderation, thus potentially influencing students’ understanding. In addition, Islamic Religious Education (PAI) learning also faces individual problems such as low learning motivation, difficulties in understanding the material, and the suboptimal practice of religious values. This study aims to examine the dynamics of students’ individual problems and the strategies to address them in PAI learning. This research employs a descriptive qualitative approach conducted at SDN 06 Jayapura, with PAI teachers as the main informants. Data collection techniques include observation, interviews, and documentation, while data analysis uses an interactive model consisting of data reduction, data display, and conclusion drawing, with validity tested through source and method triangulation. The results show that students’ problems include difficulties in understanding the material, low learning motivation, and lack of implementation of religious values, which are caused by internal factors such as ability and psychological conditions, as well as external factors such as family, environment, and technology. The strategies implemented by teachers include an individual approach, the use of varied teaching methods, providing motivation, guidance, and collaboration with parents, with constraints including limited time, a large number of students, and diverse student characteristics. In conclusion, students’ individual problems in PAI learning are complex and require holistic handling through adaptive learning strategies and support from various parties to achieve optimal learning objectives.